Penerapan Prudential Banking Sebagai Upaya Meminimalisir Risiko Kredit Bermasalah Pada Bank Wakaf Mikro Di Era Digitalisasi - Yusuf; Fathmah Hanum (Tasharruf : Journal of Islamic Economics and Business, 2023)
Digital micro waqf bank financial institutions are expected to implement prudential banking to increase people's income and welfare. This study aims to analyze the management of financing products carried out by Islamic financial institutions by applying prudential banking principles. This descriptive qualitative research was written based on literacy studies. The results of this study are that by implementing prudential banking, digital micro waqf bank financial institutions can increase customer income and welfare